Persistent coxsackievirus B1 infection triggers extensive changes in the transcriptome of human pancreatic ductal cells - Buchacher Tanja; Honkimaa Anni; Välikangas Ttommi; Lietzén Niina; Hirvonen M Karolina; Laiho Jutta E; Sioofy-Khojine Amir-Babak; Eskelinen Eeva-Liisa; Hyöty Heikki; Elo Laura L; Lahesmaa Riitta (Elsevier, 2025)
Enteroviruses, particularly the group B coxsackieviruses (CVBs), have been associated with the development of type 1 diabetes. Several CVB serotypes establish chronic infections in human cells in vivo and in vitro. However, the mechanisms leading to enterovirus persistency and, possibly, beta cell autoimmunity are not fully understood. We established a carrier-state-type persistent infection model in human pancreatic cell line PANC-1 using two distinct CVB1 strains and profiled the infection-induced changes in cellular transcriptome. In the current study, we observed clear changes in the gene expression of factors associated with the pancreatic microenvironment, the secretory pathway, and lysosomal biogenesis during persistent CVB1 infections. Moreover, we found that the antiviral response pathways were activated differently by the two CVB1 strains. Overall, our study reveals extensive transcriptional responses in persistently CVB1-infected pancreatic cells with strong opposite but also common changes between the two strains.